A cracked-hinge approach to modelling high performance fiber-reinforced concrete. (1st October 2021) - Martinelli, Enzo; Pepe, Marco; Penna, Rosa; Feo, Luciano
Abstract: This paper proposes a meso -mechanical formulation aimed at explicitly simulating the contribution of both fibers and matrix in the cracking response of fiber-reinforced cementitious composite members subjected to bending actions. Specifically, based on an extension of a previous study inspired by the well-known non-linear cracked-hinge model, the present formulation is tailored for the case of High-Performance Concrete matrices whose specific features emerge from the observation of some experiments, presented in recent studies. The comparison between those experimental observations and the numerical results obtained in the present paper demonstrates the mechanical consistency of the aforementioned assumption. Moreover, they show the "saturation effect" of the fiber contribution, already observed experimentally in other studies available in the literature and points out the need to define an effective volume fraction for the specimens with higher quantities of fibers. A parametric analysis proposed in the final section of the paper shows the influence of the volume fraction on the main mechanical parameters characterising both the cracking phenomenon and the post-cracking response of High-Performance Fiber-Reinforced Concrete members in bending.